DMS/O/P cycling in coastal NE subarctic Pacific phytoplankton assemblages exposed to elevated irradiance and photosynthetic inhibition (2022-2023) - Mcnabb, Brandon; Tortell, Philippe (SEANOE, 2024)
This dataset is associated with the article "A photo-protective antioxidant function for DMSO in marine phytoplankton" submitted for review in Nature. The primary data consists of concentrations and biological turnover rates from native and isotopically-labelled (D6/13C) DMSP, DMS and DMSO tracers in 10 deck-board incubation experiments using natural phytoplankton assemblages in the NE subarctic Pacific (i.e. coastal Vancouver Island, BC, Canada). The data includes results from experiments manipulating surface irradiance exposure (low vs. high light) in phytoplankton assemblages taken from variable depths to simulate the effects of vertical mixing-induced photic stress (n = 7), as well as photosynthethic electron transport inhibition experiments (n = 3) using the inhibitior DCMU (3-(3,4-dichlorophenyl)-1,1-dimethylurea). Ancillary data includes photo-physiology measurements (i.e. the maximum quantum yield of photochemistry at PSII, Fv/Fm, and Stern-Volmer non-photochemical quenching, NPQsv), HPLC pigments, and CHEMTAX input parameters and outputs used to derive phytoplankton community composition in some experiments.